Low complement levels in paediatric systemic lupus erythematosus and the risk of bacteraemia. (21st August 2013) - Hagen, Jaap P; Hissink Muller, Petra C E; Bredius, Robbert G M; ten Cate, Rebecca
Abstract : This report describes an 11-year-old girl with systemic lupus erythematosus (SLE) with long-standing low levels of complement proteins. A disease period with lupus nephritis (class IIIa) was complicated by Staphylococcus aureus bacteraemia and osteomyelitis. She was treated with high-dose immunosuppressants and 6 weeks of high-dose intravenous antibiotics. The clinician should be aware of bacteraemia in SLE with secondary complement deficiency.